Potential Embolic Sources Differ in Patients With Embolic Stroke of Undetermined Source According to Age: A 15-Year Study - Hou, Yan; Elmashad, Ahmed; Staff, Ilene; Alberts, Mark; Nouh, Amre (Frontiers in Neurology, 2022)
Introduction: Understanding the potential embolic source in young ESUS patients may improve the diagnosis and treatment of such patients. Hypothesis: Potential embolic sources (PES) differ in young vs older patients with ESUS, and therefore not all ESUS patients have the same risk profile for stroke recurrence Methods: Young patients (age 18-49) with ESUS who were admitted to our stroke center from 2006 to 2019 were identified retrospectively and matched with next consecutive older patients (age 50-99) with ESUS by admission date. PES were categorized as atrial cardiopathy, AFib diagnosed during follow up, left ventricular disease (LVD), cardiac valvular disease (CVD), PFO or atrial septal aneurysm (ASA) and arterial disease. Patients who had cancer or thrombophilia were excluded. Rate of type and number of PES and stroke recurrence were determined and compared between young and older patients. Results: In young patients (55.3% women, median age 39 years), the most common PES was PFO/ASA and rate of other PES was low (2-7%). Half young patients (54.1%) had a single PES, only 10% had multiple PES, and 35.3% of young patients didn’t have any PES identified. In older patients (41.7% women, median age 74 years), the 3 most common PES were atrial cardiopathy (38.1%), LVD (35.7%), and arterial disease (23.8%). Nearly half older patients (42.9%) had multiple PES. The rate of stroke recurrence tended to be lower in young patients as compared to older patients (4.9% vs. 11.4%, p=0.29). During a median follow up of 3 years, only 3 young patients (4.9%) had recurrent stroke, two of them had unclosed PFO. There were no recurrent strokes among young patients with no PES identified. Conclusions: PES differs in patients with ESUS according to age and difference in recurrence were noted. PFO is the only common PES in young patients with ESUS. Future studies prospectively evaluating PES in both age groups are needed.